Analysis of Cooperative Learning Reviewed From The Activities of Science Learning of Elementary School Teacher Education Students Science Teaching Materials Development - Abdullah, Fadila; Arbain, Rukmin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted to determine the effect of the cooperative learning model on improving learning outcomes science concentration student Muhammadiyah University of Magelang Primary teacher education. Therefore,in the learning process, the model used by the researcher is the cooperative learning model.The type of research used is experimental research with research design One Group Pretest-Posttest Design. The study’s sample consisted of 27 studensts from the science concentration class. The instrument used in this study was a multiple choice question (PG) with 10 items. The results showed that with menunjukkan tcount > ttable at 5% significance level (8.69 > 2.060) and P value < 0.050. Based on the results of the study, it can be concluded that the use of cooperative learning models, there is an increase in student learning outcomes in the Science Concentration class at Muhammadiyah University of Magelang for elementary school teacher education.